Phytochemical profile of Nauclea latifolia leaf extract: a quantitative and qualitative evaluation for anti-inflammatory and antidiabetic potential - Adepoju, Adewusi John; Esan, Akintomiwa Olumide; Olawoore, Ibidotun Theophilus; Omodara, Niyi Basil; Toromade, Taofeek Temitope (Eclética Química, 2026)
Antioxidant agents are essential for the body because of their ability to scavenge free radicals. Medicinal plants contain phytochemicals that act as antioxidants. In this study, phytochemicals, antibacterial, antioxidant, antidiabetic, and anti-inflammatory activities of leaf extracts from Nauclea latifolia were evaluated. Secondary metabolites, including saponins, alkaloids, flavonoids, tannins, coumarin, steroids, terpenoids, cardiac glycosides, glycosides, quinones, and polyphenols, were present. The ethanolic extract had the highest quantity of polyphenols (5.6±0.1 mg/g GAE), flavonoids (53.4±0.1 mg/g QE), tannins (3.8±0.1 mg/g TAE), alkaloids (30.3±0.1 mg/g), and saponins (48.10 mg/g). Intense antimicrobial action was observed against the selected pathogenic species. The ethanolic extract exhibited exceptional antioxidant activity, indicated by its low IC50 value of 2.11 mg/mL and strong reducing power. More importantly, the ethyl acetate extracts also markedly inhibited pancreatic α-amylase (IC50=2.19 mg/mL) and bovine serum albumin (IC50=2.52 mg/mL). These findings demonstrate that Nauclea latifolia is a rich source of bioactive compounds with significant medicinal potential, including antimicrobial, antioxidant, anti-inflammatory, and antidiabetic properties. These attributes highlight its suitability for various therapeutic applications.